The roles of AMP-activated protein kinase and uncoupling protein-3 in skeletal muscle fuel metabolism - Costford, Sheila (University of Ottawa (Canada), 2008)
The prevalence of obesity has increased at an alarming rate over the past few decades. Obesity is caused by a positive energy balance and is associated with several major health risks, such as cardiovascular disease, type 2 diabetes mellitus (T2DM) and some cancers. This research focuses on two proteins involved in energy regulation: AMP-activated protein kinase (AMPK) and uncoupling protein-3 (UCP3). AMPK functions to maintain cellular and whole body energy homeostasis. Studies in experimental animals have demonstrated that activation of AMPK in skeletal muscle protects against insulin resistance, T2DM and obesity. The first objective of this research was to determine whether R225W, a rare mutation in the muscle-specific gamma3 subunit of AMPK, affects activity and function in human muscle. R225W was associated with increased basal and AMP-stimulated AMPK activities, increased muscle glycogen and decreased intramuscular triglyceride (IMTG). These findings are consistent with an important role for AMPKgamma3 in human muscle energy metabolism and highlight the attractiveness of this gamma isoform as a pharmaceutical target for the treatment of metabolic disorders associated with obesity, such as T2DM. UCP3 is a poorly understood mitochondrial inner membrane protein expressed predominantly in skeletal muscle. Although the function of UCP3 is unknown, the literature supports roles for UCP3 in facilitating fatty acid oxidation and mitigating oxidative stress. Moreover, lower levels of UCP3 have been observed in muscle of T2DM patients. The second objective of this research was to determine if UCP3 protects from the development of insulin resistance. UCP3 -/-, wildtype, and UCP3tg overexpressor mice were fed a 10% or 45% fat diet for 4 or 8 months. Although UCP3 overexpression protected against the accumulation of IMTG, paradoxically, both UCP3tg and UCP3 -/- mice were protected from the development of glucose intolerance and insulin resistance. UCP3tg mice were, however, protected from the development of obesity, whereas UCP3 -/- mice were not. These results therefore support a role for UCP3 in preventing the accumulation of triglyceride in both muscle and adipose tissue. It is anticipated that these findings will lead to a better understanding of the mechanisms involved in the development of disorders of energy regulation.
Keywords: Chemistry, Biochemistry.